A NON-DICHOTOMIZING APPROACH TO LANGUAGE ISSUES IN PARKINSON'S DISEASE: HESITATIONS - Nascimento, Julyana Chaves; Chacon, Lourenco [UNESP] (Univ Estadual Campinas, Inst Estudos Linguagem, 2018)
In this article, we reflect about language facts that occur in brain-injured subjects. In order to reach our goals, we turn critically to the way biomedical literature has studied speech problems in Parkinson's disease. We have identified in this literature, for example, dissociations between language and speech or between aspects considered of motor nature and other aspects of speech/language. Based on Coudry's (1988; 2002) postulates on the complexity of the interrelationship between brain and language, we problematize the mentioned dissociations, in favor of associations between motor and discursive aspects in Parkinson's disease. We analyzed hesitations in the conversation between a Parkinsonian and a researcher subject. We understand hesitation as a discursive event related both to the process of the subject's constitution and to the process of discourse constitution. Based on Authier-Revuz's ideas, we assume that hesitation, as a form of shown heterogeneity, indicates the negotiation of the subject with the multiple other constituents of discourse. In the analysis, we observe that the hesitation indices a moment when the subject changes his position, as well as a moment in which the discursive other - health-illness - could erupt (or erupts) in the discursive chain. We observed the presence of motor aspects in the articulatory plane of speech, in the occurrence of hesitation. However, we highlight that these aspects of motor base are submitted to discursive facts, what shows, in the appearance of the hesitation in the speech of parkinsonian subjects, that the language issues in these subjects point substantially more to the nature of integrated processes, instead to the specific functions in the relations between brain and language.
Keywords: Parkinson Disease; discourse; hesitation